The Evolution of Buyer-Seller Relationships in the Digital Age: A Philosophical Approach - Leonidou, Erasmia (My University, 2025)
Rapid technological advancements have led to a significant diversification in the media through which buyers and sellers interact. This shift encompasses a broad spectrum of communication channels, extending beyond in-person communication to include technology-driven and multiformat interfaces. Digitalization and staggering amounts of information have played a catalytic role in reshaping and reassessing the relationship between informed buyers and sellers. This chapter draws on the literature of Service-Dominant Logic and Service Ecosystems by incorporating a philosophical depth to address the emerging challenges. In the same vein, this chapter tries to shed light on the interplay between individual seller capabilities and broader institutional arrangements, emphasizing the need for sellers to act as drivers of both institutional and societal well-being. Finally, this chapter offers further conceptual insights and outlines key challenges while framing the path ahead for continued exploration in the field of sales.
Keywords: Selling; Value Creation